Comparative Analysis of Companies' Financial Performance Before and After Mergers and Acquisitions (Study on Companies Listed on the IDX and Conducting Mergers and Acquisitions in 2017) - Binti Shoimaturrohmah; Makhmud Zulkifli (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the differences in the company's financial performance between before and after mergers and acquisitions. The financial performance used in this study is data three years before and three years after mergers and acquisitions. In this study, the company's financial performance was measured using seven ratios. The ratios used include Quick Ratio (QR), Return On Assets (ROA), Return On Equity (ROE), Debt Ratio (DR), Debt To Equity Ratio (DER), Total Assets Turnver (TATO) and Earning Per Share ( EPS). The sample used in this study were 5 companies that carried out mergers and acquisitions in 2017 and were listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling method. The data analysis technique in this research is descriptive statistical analysis. Testing the normality of the data using the One Sample Kolmogorv Smirnov test. The different test used was the Paired Samples T-test for data that was normally distributed and the Wilcoxon Signed Rank test for data that was not normally distributed. The results of this study indicate that QR and DER show a significant difference between the three years before and three years after mergers and acquisitions. While the other ratios, namely ROA, ROE, DR, TATO, and EPS showed no significant difference between before and after mergers and acquisitions.